Land Disputes between the Catholic Church and Indigenes of Weh Fondom, 1957-1996 - Lang, M.K. (Ghana Social Science Journal, 2017)
An important goal of church planting and growth in Africa was to acquire land required for the provision of public goods such as schools, clinics and cemeteries. This made the church become the owner of relatively large parcels of land in communities across Africa. As would be expected, the increasing competition over land and the ensuing conflicts which have become more and more common in the continent have not left the church unaffected. Indeed, episodes of conflict over land between churches and host communities are common in Africa‘s land conflict history. This paper, based on primary and secondary data, provides evidence of land conflicts between churches and members of host communities. The Roman Catholic Church in Weh in the Northwest of Cameroon is used as a case for examining the issue. Informed by the conflict theory, the paper attempts an analysis of the underlying factors, dynamics and settlement of land disputes involving the church and some Weh indigenes. The study reveals that the mounting wave of land disputes between the Catholic Church and Weh indigenes that manifested itself in the form of conflicting borderlines and competing ownership claims which were brought about by both informal and formal institutions charged with the resolution of such conflicts. While some of the disputes were laid to rest, others remain unsolved due to the inefficiency of customary and statutory land conflict resolution bodies as well as the attitude of the disputants. It is, therefore, time for land administration systems to be enhanced and developed to end the maldistribution of land, forestall land disputes or minimize their occurrence, and achieve a quick and effective resolution of such conflicts. The paper concludes that the Catholic Church and its host communities need to rethink their land deals
Ghana Social Science Journal, 14(1), 109-138
Keywords: Land; conflict; Roman Catholic Church; Weh; Land Tenure